Peter Warlock: a study of the composer through the letters to Colin Taylor between 1911 and 1929 - Smith, Barry, 1939- (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1991)
This thesis involves a comprehensive study of the letters written by Philip Heseltine (Peter Warlock) to Colin Taylor from 1911 to 1929. Warlock first came into contact with Taylor at Eton in 1908 when he studied the piano with him as a schoolboy. Through Taylor's imaginative teaching during the next four years Warlock's interest in and understanding of music, particularly modern music, grew and matured. At the same time a strong bond of friendship developed between the two men and continued until Warlock's early death in 1930. This is clearly illustrated in the surviving 87 letters. Warlock was a great letter writer and over a thousand of them have been preserved, mostly in the British Library. His letters to Taylor have a special significance in that they were written during the entire period of his adult life, most of them during the early formative and creative years. They cover a wide range of topics including the influential friendships with the composers Frederick Delius and Bernard van Dieren, contemporary British and foreign music and his own work as a composer, writer, and scholar. They also give us many important insights into his life and personality, written as they are with rare candour and humour. In this thesis each letter has been carefully and systematically studied and the resulting information used to augment and expand the existing knowledge of Warlock's life and personality, his friendship with Taylor, his music and writings. Because of the wide field which the life and works of Peter Warlock cover, this study has been limited to subjects arising out of the correspondence with Taylor. Where necessary, additional information has been interpolated from other sources, mainly to give a sense of continuity and to explain references which might otherwise seem obscure. For a detailed study of Warlock's music readers are referred to Ian Copley's book, The Music of Peter Warlock, (Dennis Dobson, London, 1979). A definitive biography has yet to be written.
Keywords: Warlock, Peter, 1894-1930 -- Correspondence; Taylor, Colin, 1881-1973 -- Correspondence; Composers -- England -- Correspondence